HUBUNGAN ANTARA ALAM DAN MANUSIA MENURUT PANDANGAN ISLAM - Nanang Jainuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This paper delves into the concept of the relationship between nature and humans from an Islamic perspective. This relationship portrays how humans, as stewards (khalifah), bear the responsibility of preserving and nurturing the environment in line with religious and ethical values. In the Quran and Hadith, there are directives emphasizing the importance of maintaining a balance between humans and nature, while also underscoring the role of humans as caretakers of the Earth. The creation of the universe by Allah showcases its beauty and diversity, with humans elevated as stewards tasked with judiciously safeguarding and utilizing nature. This concept provides guidance on sustainable management and environmental protection. The Quranic verses and the Hadiths of the Prophet Muhammad underline the significance of caring for nature, avoiding wastefulness of resources, and preserving ecological balance. Islam's perspective on humans as stewards emphasizes moral responsibility and ethics in treating nature with a deep sense of duty. By adhering to these teachings, humans can fulfill their role as custodians of the Earth in a wise and sustainable manner